Wilhelm Sasnal - Painting as prop - Szymczyk, Adam 1970-; Banai, Noit; Haidu, Rachel ca. 20./21.Jh; Loock, Ulrich 1953- (Stedelijk Museum, 2024)
Coinciding with the eponymous exhibition at the Stedelijk Museum Amsterdam, Painting as Prop features four new essays and a conversation with Polish painter Wilhelm Sasnal. Throughout his career, the artist has consistently offered reinterpretations of existing imagery, whether an artwork, a newspaper image, or a book. Other paintings, some of which played a role as props in Sasnal’s recent film project, "The Assistant", take cues from archival images, banal snapshots, popular culture, and art history. All of the paintings were made between 2002 and 2024. The texts introduce Sasnal’s distinct portraiture, modernist inspirations, and the evolution of his first feature film
Impressum: This book was published in conjunction with the exhibition "Wilhelm Sasnal - Painting as Prop", Stedelijk Museum Amsterdam, March 30, 2024 - September 1, 2024
Print run: 1500
Keywords: Sasnal, Wilhelm -- 1972-; Geschichte 2002-2024; Ölmalerei; Ausstellungskatalog -- Stedelijk Museum Amsterdam -- 30.03.2024-01.09.2024 -- Amsterdam